FACTORS INFLUENCING COMPETITIVENESS OF SMEs IN NAIROBI COUNTY, KENYA - Irungu, Anne Waithera; Arasa, Prof. Robert (International Journal of Entrepreneurship and Project Management, 2017)
Purpose: The purpose of this study was to determine the factors influencing organizational competitiveness among the Small and Medium Enterprises in Nairobi County, Kenya Methodology: The study adopted a descriptive research design. The population comprised of top 100 SMEs SMEs. A sample size of 25 SMEs which represented 30% of the target population was selected through stratified random sampling. The study utilized primary data that was collected through questionnaire. The collected data was edited for completeness, coded and transcribed into Statistical Package for Social Sciences (SPSS) where the data was analyzed. The data was analyzed using both descriptive and inferential statistics. The descriptive statistics that was used in the study includes the mean and standard deviations whereas the inferential statistics that the study adopted includes correlation and regression analysis. Results: The study findings indicated that the management of SMEs was concerned with attaining high profits and thus improved performance which would translate to competitive advantage. The managers therefore are putting in place various measures that are aimed at achieving sustainable competitive advantage. Correlation results indicated that strategic leadership, adoption of technology, resources availability and organization culture had a positive and significant relationship with organization competitiveness. Unique Contribution to Theory, Practice and Policy: The study concludes that strategic leadership influenced organizational competitiveness through setting of SMART goals and objectives and putting in place clear vision and mission statements to guide the company's operations. Sustainable competitive advantage of the firm stems from the effective strategic leaders, adoption of technology, resources availability and effective organization culture. The study recommends that SMEs should embrace various competitive strategies to remain relevant in the market and to beat their potential competitors. The SMEs management should develop and enhance mechanisms of gathering market intelligence, benchmarking to ensure that they meet the best standards and ensuring that they are in constant touch with their customers. This ensures continuous improvement in services and products that are centered on the customers.